Area socioeconomic status and childhood injury morbidity in New South Wales, Australia. Issue 5 (4th October 2007) - Poulos, Roslyn; Hayen, Andrew; Finch, Caroline; Zwi, Anthony
Abstract : Objective: To explore the relationship between child injury morbidity and socioeconomic status. Design: A cross-sectional analysis of routinely collected hospital separation data for unintentional injury for the period 1999/2000–2004/2005. Setting: All statistical local areas of New South Wales (NSW), Australia Subjects: 110 549 unintentional injury-related hospital separations for NSW children aged 0–14 years. Main outcome measure: Adjusted incidence rate ratios (IRRs) for hospital separations for unintentional injury (for all injury and by individual injury mechanisms) by quintile of socioeconomic disadvantage for children aged 0–14 years. Results: There was no clear relationship between socioeconomic status and injury when all injury mechanisms were combined. However, children in the more disadvantaged quintiles were more likely to be hospitalized than children in the least disadvantaged quintile for the following injury mechanisms: motor cycle (point estimates for IRRs across the socioeconomic status quintiles ranged from 2.95 to 4.02 relative to the least disadvantaged quintile), motor-vehicle occupant (IRR range 1.33–2.27), pedestrian (IRR range 1.43–2.54 for ages 0–4 years), pedal cyclist (IRR range 1.30–1.50), fire and burns (IRR range 1.37–2.00), and poisoning (IRR range 1.32–1.91). Similarly, hospital separation rates for foreign body, other transport, and pedestrian (aged 5–9 years) injuries were also greater, but the differences were not statistically significant across all quintiles. These injury mechanisms accounted for about 25% of the hospital separations. Conclusions: The relationship between relative socioeconomic disadvantage and injury risk in NSW children is strongest for transport-related injuries, fires and burns, and poisoning. Interventions that address these specific injury mechanisms may help to reduce the disparity between high and lower socioeconomic groups.